Pediatric COVID-19 and Appendicitis: A Gut Reaction to SARS-CoV-2?. Issue 2 (8th December 2020) - Malhotra, Amisha; Sturgill, Marc; Whitley-Williams, Patricia; Lee, Yi-Horng; Esochaghi, Chika; Rajasekhar, Hariprem; Olson, Birk; Gaur, Sunanda
Abstract : Background: We describe the temporal pattern of COVID-19 admissions to a tertiary care children's hospital in central New Jersey during the SARS-CoV-2 surge, covering the time period from March 29 to July 26, 2020. Methods: Medical charts were reviewed for the date of admission, past medical history, and demographic variables, presenting signs and symptoms, admitting laboratory values, diagnostic imaging, diagnosis, treatment modalities, and outcomes including length of stay and disease severity. Results: Patients with symptomatic SARS-CoV-2 infection tended to present with pneumonia early during the study period, which coincided with the early surge in New Jersey cases. Approximately 2 weeks after the peak in reported SARS-CoV-2 cases in New Jersey, we began to see fewer pneumonia cases and an increase in admissions for Multi-Inflammatory Syndrome in Children and cases of acute appendicitis in association with a diagnosis of SARS-CoV-2 infection. Conclusions: We present a novel association of acute appendicitis in children infected with SARS-CoV-2 and postulate that it may represent a postinfectious hyperinflammatory complication of SARS-CoV-2 infection occurring 2 weeks after the early manifestation of acute pneumonia disease in children.